Subtalar arthroeresis in the treatment of planovalgus feet deformity: the pros and cons (the review of literature) - Korolkov, Oleksandr; Rakhman, Paviel; Kikosh, Gennadiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The paper presents an analysis of the scientific literature on the treatment of plano-valgus deformity of the foot (PVDF) in adults and children using subtalar arthroeresis. The indications and contraindications for this intervention discussed and possible complications are shown.It is shown that, on the one hand, most authors emphasize quite high efficiency of the said intervention (from 60 to 95.4 % of excellent and good results) in the presence of the other undoubted benefits — less traumatic and minimally invasive, relative cheapness, early verticalization and timely rehabilitation that meets modern requirements in orthopedics.On the other hand, the method could provoke different complications that do not exclude the repeated interventions and the development of irreversible states in the posterior part of foot.An algorithm choosing the optimal treatment PVDF in children, including the conditions of cerebral palsy, depending on the grade of foot deformity and characteristics of movement disorders, has not worked out yet. There are no generally accepted clinical-radiographic criteria for the choosingof type and size of implant. Determining the indications and contraindications for subtalar arthroeresis requires clarification in children of different age groups.The issue of early postoperative treatment and further rehabilitation patients (both children and adults) were not practically highlighted. Combination of subtalar arthroeresis with other interventions in different parts of the foot and various anatomical structures (soft tissue and bone) depending on the patient’s age and degree of foot deformity remains to be a questionable issue. The authors emphasize that today no papers are found in the scientific literaturethat meet the high level of evidence and efficacy of use of sutalar arthroeresis in the conditions of PVDF in children and adults.